2001
DOI: 10.1677/joe.0.1700653
|View full text |Cite
|
Sign up to set email alerts
|

Programming hyperglycaemia in the rat through prenatal exposure to glucocorticoids-fetal effect or maternal influence?

Abstract: In a previous study, we showed that exposure of rats to dexamethasone (Dex) selectively in late pregnancy produces permanent induction of hepatic phosphoenolpyruvate carboxykinase (PEPCK) expression and hyperglycaemia in the adult offspring. The mechanisms by which glucocorticoids cause this programming are unclear but may involve direct actions on the fetus/neonate, or glucocorticoids may act indirectly by affecting maternal postnatal nursing behaviour. Using a cross-fostering paradigm, the present data demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
3
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 40 publications
4
127
3
4
Order By: Relevance
“…Trunk blood plasma corticosterone levels were similar in SHAM and CORT rats ( Fig. 1), and elevated relative to the normal circadian mean (26,27).…”
Section: Effect Of Modifying Plasma Corticosterone Levels In Adult Dementioning
confidence: 72%
“…Trunk blood plasma corticosterone levels were similar in SHAM and CORT rats ( Fig. 1), and elevated relative to the normal circadian mean (26,27).…”
Section: Effect Of Modifying Plasma Corticosterone Levels In Adult Dementioning
confidence: 72%
“…It would also appear that cross-fostering per se may not be without significant effects on maternal behaviors (Maccari et al, 1995) and has been reported to reduce baseline and nicotine-stimulated DA secretion in the nucleus accumbens (Kane et al, 2004). On the other hand, certain programming effects of prenatal dexamethasone treatment were unaffected by cross-fostering to control dams, suggesting that the GC effects operate directly in the fetus (Nyirenda et al, 2001). On balance, the foregoing considerations illustrate the value of selecting a minimally intrusive treatment protocol, along with exposure to modest doses of dexamethasone, as a valid approach to investigating neurobiological programming by GCs.…”
Section: Dexamethasone Treatment Regimensmentioning
confidence: 99%
“…Hyperglycemia, impaired insulin secretion, insulin resistance, and even frank diabetes in the offspring have been induced by some prenatal maneuvers with or without IUGR (55,60 -66). Underlying mechanisms may include decreased number of pancreatic ␤ cells (67)(68)(69), upregulation of hepatic enzymes that may convey insulin resistance (55,60), and upregulation of the glucocorticoid receptor (60,70,71). In contrast, Gatford et al (72) reported that 5-yr-old sheep made that were hypertensive by prenatal administration of dexamethasone exhibited unchanged insulin sensitivity.…”
Section: Characteristics Of Disease In Offspringmentioning
confidence: 99%